CLASSROOM MANAGEMENT PRACTICE BETWEEN URBAN AND RURAL EFL TEACHERS - Hami Mukaromah; Ateng Kurnia; Amir Hamzah (Institut Pendidikan Indonesia Garut, 2023)
Classroom management has a crucial role in teaching and learning. Classroom management involves aspects of teaching that are central to student learning and teacher success. Unfortunately, Urban and Rural EFL teachers often have difficult to face disciplinary problems and student’s misbehavior. The study aimed to analyzedifferences and the similarities of the classroom rules in the classroom management practice between urban and rural EFL teachers. To achieve the aforesaid purpose, this study employed a qualitative method including comparative analysis research design. The data collected through the interview. Two EFL teachers in different districts of Senior High Schools in West Java, Indonesia which is in urban and rural districts purposively selected as the participant. The finding showed that there were five characteristics of classroom rules considered similar between urban and rural EFL teachers, they were created collaboratively with students, specific in nature, publicly posted, taught to students, and clearly tied to positive and negative consequences. Moreover, there were differences in two characteristics, there were a number of rules and stated positively.